Dental Students' Perceptions of Digital Assessment Software for Preclinical Tooth Preparation Exercises. Issue 5 (1st May 2017) - Park, Carly F.; Sheinbaum, Justin M.; Tamada, Yasushi; Chandiramani, Raina; Lian, Lisa; Lee, Cliff; Da Silva, John; Ishikawa-Nagai, Shigemi
Abstract : Objective self‐assessment is essential to learning and continued competence in dentistry. A computer‐assisted design/computer‐assisted manufacturing (CAD/CAM) learning software (prepCheck, Sirona) allows students to objectively assess their performance in preclinical prosthodontics. The aim of this study was to evaluate students' perceptions of CAD/CAM learning software for preclinical prosthodontics exercises. In 2014, all third‐year dental students at Harvard School of Dental Medicine (n=36) were individually instructed by a trained faculty member in using prepCheck. Each student completed a preclinical formative exercise (#18) and summative examination (#30) for ceramometal crown preparation and evaluated the preparation using five assessment tools (reduction, margin width, surface finish, taper, and undercut) in prepCheck. The students then rated each of the five tools for usefulness, user‐friendliness, and frequency of use on a scale from 1=lowest to 5=highest. Faculty members graded the tooth preparations as pass (P), marginal‐pass (MP), or fail (F). The survey response rate was 100%. The tools for undercut and taper had the highest scores for usefulness, user‐friendliness, and frequency of use. The reduction tool score was significantly lower in all categories (p<0.01). There were significant differences in usefulness (p<0.05) and user‐friendliness (p<0.05) scores among the P, MP, and F groups. These results suggest that the prepCheck taper and undercut tools were useful for the students' learning process in a preclinical exercise. The students' perceptions of prepCheck and their preclinical performance were related, and those students who performed poorest rated the software as significantly more useful.